Measuring Consumer Involvement and Product Attributes on Beef Consumer Segmentation - Mujtahidah Anggriani Ummul Muzayyanah; Agung Triatmojo; Nguyen Hoang Qui (Caraka Tani: Journal of Sustainable Agriculture, 2023)
Involvement is crucial in explaining emerging consumer behavior, such as purchasing and consumption decisions. Consumer involvement and purchase decisions are influenced by product attributes, resulting in differences in segmentation. Therefore, this study aims to examine consumer involvement in various beef segmentation categories and their product attributes. This would enable the profiling of consumer segmentation based on their level and type of involvement. The data were collected through an unrestricted self-selected survey run among 303 consumer and 4 consumer segments were identified. Furthermore, the One-way ANOVA F-tests with post-hoc Tukey multiple comparison test of mean scores and Pearson's chi-squared were used to achieve the second objective. The results showed concerned-consumer and cautious-consumer segment place emphasis on the economic value of the product when making purchasing decisions. In contrast, there was no distinction between functional and symbolic values of involvement in each consumer segment. This indicates that concerned-consumer, cautious-consumer, indifferent-consumer and straightforward-consumer segment perceive the advantages of purchasing beef. Furthermore, the concerned-consumer segment scored high on all product attributes. This study found that consumer with high involvement may consider a variety of factors before purchasing a product. Nevertheless, a low level of consumer involvement has less information to be apprehensive about, and improved consumer service can assist the cautious-consumer and concerned-consumer segment by simplifying the various information considered. Also, the identification of consumer segment based on balancing their attitudes towards meat consumption is of fundamental importance for the development of strategies in the red meat sector. The formulation of the market orientation has implications for product differentiation and marketing communication strategies.